Los Estudios Sociales de cara a la Historia: Provocaciones para un debate urgente - González Sanchez, David E. (Universidad de Costa Rica, 2020)
This essay proposes to discuss the meanings that have been given to social studies at the School of History of the National University of Costa Rica, particularly in the speeches present in the study programs and academic articles. The main question is what exactly means social studies beyond its traditional notion as a school subject matter To attempt an answer, I propose the thesis that Social Studies have not achieved their own academic development by being subordinated to historical discipline as a hegemonic epistemic field that instrumentalizes pedagogy by limiting the understanding of what history and social learning implies. For this, I expose three existing tensions in the history-social studies relationship. I conclude that it is not enough to establish research agendas without facing the problem of epistemic subordination that leads to the constitution of a theoretical framework that assumes the problem of teaching and learning of history and the social. Finally, I outline a strategy of reflection and epistemic reconstruction consistent with the consolidation of social studies as a research and action area with its own identity and open to horizontal dialogue with the other disciplines involved in its development.